Pengembangan Aplikasi Mobile menggunakan Metode Waterfall untuk Absensi Karyawan - Nur Hidayah; Indira Novi Yulianti; Hilaludin Hilaludin; Aries Saifudin; Teti Desyani (Teknik Informatika Universitas Pamulang, 2022)
Attendance of absences are very important activities in the employee recitation process. Companies in Indonesia have a lot of employees. Employee is a very important variable. Every company must always control every employee. Given the number of companies and employees will always increase from time to time, controlling employee attendance is very influential on a company. Many companies still use manual attendance, especially in small companies. In addition, another problem that arises is the lack of control over employee attendance, manual attendance systems can be easily manipulated and not very effective which can hinder the company's progress performance. when you come and go home. The system designed must be able to meet user needs such as the problems that have been described. In addition, the application must be able to collect data on incoming and outgoing employees to control attendance. This attendance system was created using Waterfall and implemented in Android devices. In addition, a system is also created to control employee attendance, employee discipline, and improve the effectiveness and efficiency of the attendance system. In this application, employees can check in and check out to control attendance.